Engineering Synechocystis PCC6803 for Hydrogen Production: Influence on the Tolerance to Oxidative and Sugar Stresses - Ortega-Ramos, Marcia (Public Library of Science, 2014)
In the prospect of engineering cyanobacteria for the biological photoproduction of hydrogen, we have studied the hydrogen production machine in the model unicellular strain Synechocystis PCC6803 through gene deletion, and overexpression (constitutive or controlled by the growth temperature). We demonstrate that the hydrogenase-encoding hoxEFUYH operon is dispensable to standard photoautotrophic growth in absence of stress, and it operates in cell defense against oxidative (H(2)O(2)) and sugar (glucose and glycerol) stresses. Furthermore, we showed that the simultaneous over-production of the proteins HoxEFUYH and HypABCDE (assembly of hydrogenase), combined to an increase in nickel availability, led to an approximately 20-fold increase in the level of active hydrogenase. These novel results and mutants have major implications for those interested in hydrogenase, hydrogen production and redox metabolism, and their connections with environmental conditions.